PENERAPAN PRINSIP SYARIAH DALAM PERMODALAN BANK SYARIAH - Danang Wahyu Muhammad (Jurnal Media Hukum, 2014)
Islamic Bank  is a bank  that  is based on Syariah principles. The principles must  always be obeyed both  in  the establishment and  in the operational,  including  the  financial capital.  Regarding  the capital,  it must not come from  a  source  that  is  considered  as  haram  according  to  Syariah  principles, which will  cause  a mix  between halal  and  haram.  Something  that  is  halal must  be  strictly  separated  from  something  that  is  haram,  and  vice versa. This paper discusses The Application of Syariah Principles in Islamic Bank Capitalization. Several principles are  applied  and must  be  obeyed by  Islamic  Bank,  namely: Al-Ta’awan  Principle,  Principle  of Avoiding  (Al-Ikhtinaz)  from  gharar, masyir,  and  riba.  As  a  part  of Islamic  Economy,  the  activities  of  Islamic  Bank  can  be observed  from  four  points  of  view,  namely;  ilahiyah  economy,  ahlaq  economy, humanity  economy,  and balance economy. Meanwhile, from several viewsnof Muslim Economists,  it can be concluded that the core of Islamic  teaching  is  tauhid, which means  that  all  human  activities  in  the world,  including economy,  is merely for  ibadah  –  act  of  devotion  – which  is  aimed  at  following  one  law,  Allah’s  law.  The  value  of  tauhid,  in practice,  is  interpreted  in many  valaes  and  there  are  three basic  values  that  become distinguishing factors between  Islamic economy and other, namely adl, khilafah, and takaful.  It can be conladed that  is a possibility that  Syariah  Principles  are  violated  by  Islamic  Bank  in  terms  of  its  capitalization.  This  can be  see  from  the missing of requirements that make it compulsory for all founders to make a statement letter which states that the  financial  capital  deposited  to  Islamic  Bank  does  not  come  from  a  source  which  is  considered as  haram according  to Syariah  Principle.  The  consequence  of  the missing requirement  is  the  possibility of  receiving haram  financial  capital  from the  founders.  Should  this happen,  then Syariah Principle  is violated.